Consider the following equation (proved).
a = b a × a = b × a a 2 = a b a 2 − b 2 = a b − b 2 ( a + b ) ( a − b ) = b ( a − b ) a + b = b b + b = b 2 b = b 2 = 1
Is the proof correct?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Log in to reply
Going by the fundamental definition , the expression (a/a = 1) for all real values of a except '0'.
Log in to reply
That's called a math fallacy. Even is a-b = 0, the equation satisfies, so that step is correct. Let me post an answer.
No, this solution is absolutely correct
Given in the question that a=b ,
→ a - b = 0 ,
Therefore after the fourth step, where
(a - b) was cancelled , it was a mistake because in mathematics , division by zero is not possible !
The cancelling step is skipped. So there is no step where I cancelled the (a-b) on both sides. Check again. The fifth step is where it is wrong.
Log in to reply
Ok got this thank you! But maybe the seniors could explain it in some other interesting way.
a = b ⟹ a − b = 0 Now in 5 t h step, We have divided both sides by ( a − b ) , ie. dividing by 0 what in turn gives 0 0 . Which is undetermined
@Vicky Vignesh Instead of asking if the proof is correct or not, you should have asked which step was wrong. It is obvious that 2 is not equal to 1. So the proof has to be false.
Log in to reply
Yeah. Still, since this has been proved in a fallacy , users might get confused! So, True / False is better.
Log in to reply
Then please rephrase the question to this ......... proof is correct. Is this statement true or false.
There's still some doubt here , @Calvin Lin sir please comment !
@Ashish Siva , @Svatejas Shivakumar , @Hung Woei Neoh , please do comment & clarify this concept!
Log in to reply
The answer is correct. The steps are all correct till the 6th step. In this they have cancelled off (a - b) from the numerator and the denominator. But if you see the first step, it is stated that a = b . So, a − b = 0 . So, in the fifth step can be written as ( a + b ) × 0 = b × 0 . Then we are dividing 0 by 0 by cancelling off the (a - b)'s. But 0 0 is indeterminate. So, this proof is flawed.
Log in to reply
Exactly! thnx for commenting.
Yeah! correct :)
Step 6 is clearly the wrong one. Step 6 is where we cancelled out ( a − b ) . This means we divided the equation by ( a − b ) at Step 6. This is equivalent to dividing by 0 , which does not exist.
However, the explanation given is wrong. Even if a = 0 , we cannot divide it like this, because ( a − b ) would still be 0 , which would mean that we're still dividing by 0 . The condition should be like this:
We can divide ( a − b ) if and only if a − b = 0 , or a = b
Log in to reply
Yes ur right , thnx for commenting! +1!
I understand that this concept is clear to everyone now! Nice discussion , cheers:)
The step at I which cancelled (a-b) is skipped.
And (a+b)=b only if a=0, so there applies an condition. Its not true for all numbers.
Log in to reply
@Viki Zeta – No, you don't just skip a step in proving something. There is no such thing as skipping steps in mathematical proofs.
Log in to reply
@Hung Woei Neoh – Just saying which is wrong from given and why. Anyway I agree 0/0 is not defined.
Log in to reply
@Viki Zeta – And I'm saying your explanation is not correct. Note that when you multiplied a to both sides of the equation, you were introducing extra roots to the equation. It's like saying this:
− 1 = ( − 1 ) 2 = 1 = 1
Care must be taken that you have introduced an extra root when you squared the equation. Similarly, over here, you just factorized it out like this
( a + b ) ( a − b ) − b ( a − b ) = 0 ( a + b − b ) ( a − b ) = 0 a + b − b = 0 or a − b = 0
You cannot just assume that a + b = b . In fact, it's totally irrelevant here
The proof holds up until the second to last line, provided that a = b = 0
Problem Loading...
Note Loading...
Set Loading...
If (a+b)(a-b)=b(a-b), then b=a+b if and only if a-b is not 0. However, the first step in the proof is that a=b, so a-b=0.